2017
DOI: 10.1371/journal.pone.0185079
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of 2,4 diaminoquinazoline inhibitors of the decapping scavenger enzyme DcpS: Context-specific modulation of SMN transcript levels

Abstract: C5-substituted 2,4-diaminoquinazoline inhibitors of the decapping scavenger enzyme DcpS (DAQ-DcpSi) have been developed for the treatment of spinal muscular atrophy (SMA), which is caused by genetic deficiency in the Survival Motor Neuron (SMN) protein. These compounds are claimed to act as SMN2 transcriptional activators but data underlying that claim are equivocal. In addition it is unclear whether the claimed effects on SMN2 are a direct consequence of DcpS inhibitor or might be a consequence of lysosomotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…1). We found 2B/Ϫ FVB/N mice used in this study showed no drift [median survival: 20 days, this study; 21 days, historical data; log-rank (Mantel-Cox), 2 ϭ 0.58, P ϭ 0.45] (Cherry et al 2017;Gogliotti et al 2013). Importantly, mice from the 2B/Ϫ line had a slower course of disease progression and a longer lifespan than other severe SMA mouse models (Fig.…”
Section: Survival Of 2b/ϫ Micementioning
confidence: 67%
See 2 more Smart Citations
“…1). We found 2B/Ϫ FVB/N mice used in this study showed no drift [median survival: 20 days, this study; 21 days, historical data; log-rank (Mantel-Cox), 2 ϭ 0.58, P ϭ 0.45] (Cherry et al 2017;Gogliotti et al 2013). Importantly, mice from the 2B/Ϫ line had a slower course of disease progression and a longer lifespan than other severe SMA mouse models (Fig.…”
Section: Survival Of 2b/ϫ Micementioning
confidence: 67%
“…A single nucleotide transition in SMN2 alters its splicing pattern such that only a small amount of full-length survival motor neuron (SMN) protein is produced (Lorson et al 1999). Thus SMA is caused by low levels, not the complete absence, of the essential SMN protein (Coovert et al 1997;Lefebvre et al 1997;Schrank et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data and a comprehensive study of the biological effects of DcpS inhibitors in cells in vitro and in vivo are the subject of another report. 28 Design of Matched Inactive Analogs of DcpS Inhibition. Toward our ultimate goal of understanding if the efficacy observed in SMA mouse models by administering 1 is due to DcpS inhibition or due to the physicochemical or general structural characteristics of the chemotype, we were in need of structurally similar but DcpS inactive 2,4-diaminoquinazolines as tool compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…s., 1H), 1.76 (d, J = 12.05 Hz, 2H), 1.28−1.44 (m, 2H); 13 C NMR (101 MHz, DMSO-d 6 ) δ 162.5 (d, 1 J CF = 247.51 Hz), 162.1, 161.2, 156.9, 155.6, 143.0, 132.0 (d, 3 J CF = 5.03 Hz), 129.4 (d, 3 J CF = 8.32 Hz), 125.2 (d, 2 J CF = 14.77 Hz), 124.6 (d, 4 J CF = 3.5 Hz),, 117.2, 115.5 (d, 2 J CF = 23.96 Hz), 103.8, 99.7, 73.5, 55. 3 3-((2,4-Diamino-7-methylquinazolin-5-yl)methoxy)-5-fluorobenzonitrile (28). To a solution of 55 (1.47 g, 5.171 mmol) in DMA (16 mL) was added guanidine carbonate (1.86 g, 10.3 mmol) at 10 °C.…”
Section: -((1-(2-fluorobenzylmentioning
confidence: 99%